Tenure of non-traditional animals in Ciudad Autónoma de Buenos Aires, Argentina - Escati, Lucia (2020)
The aim of this study was to know the characteristics of the possession, motivations, perceptions and behaviour of the population holding non-traditional animals in the Autonomous City of Buenos Aires (CABA), Argentina. An observational study was conducted through a survey in a general group (GG): households in an area of ​​medium socioeconomic level; in a group attending health services (GDS): people who attend the Institute of Zoonoses Dr Luis Pasteur of CABA; and in a group in risk areas (GAR): households in the Costanera Sur settlement "Rodrigo Bueno", a neighbourhood with indexes of unsatisfied basic needs. A total of 140 surveys were conducted in GG, 160 in GDS and 154 in GAR during 2017. The probability of having canine and/or feline together with non-traditional animals was 63.2% (12/19) in GG and 75% (9/12) in GAR. The possession of non-traditional animals was closely related to the customs of people who have settled in urban environments migrating from other provinces, with the need to maintain certain anthropological links and avoid uprooting. Moreover, 5.3% in GG (1/19), 20.0% in GDS (5/25) and 8.3% in GAR (1/12) mentioned that their animal had attacked. No differences were observed between groups on the perception of the risk of disease transmission. They agreed that their animals are not at risk but consider that the risk is high when these animals are in the wild.